Dedicated call center (SOS-HAE) for hereditary angioedema attacks: study protocol for a randomised controlled trial. Issue 1 (December 2016) - Javaud, Nicolas; Fain, Olivier; Durand-Zaleski, Isabelle; Launay, David; Bouillet, Laurence; Gompel, Anne; Sobel, Alain; Woimant, Maguy; Rabetrano, Hasina; Petrovic, Tomislav; Lapostolle, Frédéric; Boccon-Gibod, Isabelle; et al.
Abstract Background Despite the availability of guidelines for the specific treatment of hereditary angioedema (HAE) attacks, HAE morbidity and mortality rates remain substantial. HAE attacks are a major medical issue requiring specific treatment as well as a considerable socio-economic burden. We report a protocol designed to test whether a dedicated call centre is more effective than usual practice in the management of patients experiencing an HAE attack. Methods/design This prospective, cluster-randomised, single-blind, parallel-group, multicentre trial evaluates the morbidity and consequent socio-economic costs of the management of patients experiencing an HAE attack by a dedicated call centre as compared to usual practice. The trial aims to recruit 200 patients. Patients in the intervention arm are provided with an SOS-HAE card with the call centre's freephone number that they can access in the case of an attack. The centre's mission is to provide recommended expert advice on early home treatment. The centre can route the call to a local emergency medical service with competency in HAE management or even arrange for the drugs needed for the specific treatment of an HAE attack to be sent to the emergency department of the local hospital. The primary outcome measure is the number of hospital admissions for an HAE attack. Each patient will be followed up every 2 months for 2 years. The study has been approved by the ethics committee (Comité de Protection des Personnes d'Ile de France 10 ; registration number: 2012-A00044-39; date of approval: 19 January 2012). Discussion The SOS-HAE protocol has been designed to address the handling of attacks experienced by patients with HAE in the home. The proposed trial will determine whether the setting up of a dedicated call centre is more effective than usual practice in terms of reducing morbidity as given by the numbers of hospital admissions. The results are also anticipated to have important implications in terms of socio-economic costs for both healthcare services and patients. Trial registration ClinicalTrials.govNCT01679912 .